Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am having trouble proving this inequality in $R^3$. It makes sense in $R^2$ for the most part. Can anyone at least give me a starting point to try. I am lost on this thanks in advance.

share|cite|improve this question
Since you have proved it for $\mathbb{R}^2$, try using induction. – tcmtan Sep 12 '12 at 23:17
up vote 1 down vote accepted

You know that, for any $x,y$, we have that

$$(x-y)^2\geq 0$$


$$y^2+x^2\geq 2xy$$

Cauchy-Schwarz states that

$$x_1y_1+x_2y_2+x_3y_3\leq \sqrt{x_1^2+x_2^2+x_3^3}\sqrt{y_1^2+y_2^2+y_3^3}$$

Now, for each $i=1,2,3$, set



We get

$$\frac{y_1^2}{{y_1^2+y_2^2+y_3^2}}+\frac{x_1^2}{{x_1^2+x_2^2+x_3^2}}\geq 2\frac{x_1}{\sqrt{x_1^2+x_2^2+x_3^2}}\frac{y_1}{\sqrt{y_1^2+y_2^2+y_3^2}}$$

$$\frac{y_2^2}{{y_1^2+y_2^2+y_3^2}}+\frac{x_2^2}{{x_1^2+x_2^2+x_3^2}}\geq 2\frac{x_2}{\sqrt{x_1^2+x_2^2+x_3^2}}\frac{y_2}{\sqrt{y_1^2+y_2^2+y_3^2}}$$

$$\frac{y_3^2}{{y_1^2+y_2^2+y_3^2}}+\frac{x_3^2}{{x_1^2+x_2^2+x_3^2}}\geq 2\frac{x_3}{\sqrt{x_1^2+x_2^2+x_3^2}}\frac{y_3}{\sqrt{y_1^2+y_2^2+y_3^2}}$$

Summing all these up, we get

$$\frac{y_1^2+y_2^2+y_3^2}{{y_1^2+y_2^2+y_3^2}}+\frac{x_1^2+x_2^2+x_3^2}{{x_1^2+x_2^2+x_3^2}}\geq 2\frac{x_1y_1+x_2y_2+x_3y_3}{\sqrt{y_1^2+y_2^2+y_3^2}\sqrt{x_1^2+x_2^2+x_3^2}}$$

$$\sqrt{y_1^2+y_2^2+y_3^2}\sqrt{x_1^2+x_2^2+x_3^2}\geq {x_1y_1+x_2y_2+x_3y_3}$$

This works for $\mathbb R^n$. We sum up through $i=1,\dots,n$ and set

$$y=\frac{y_i}{\sqrt{\sum y_i^2}}$$

$$x=\frac{x_i}{\sqrt{\sum x_i^2}}$$

Note this stems from the most fundamental inequality $x^2\geq 0$.

share|cite|improve this answer
Peter, I appreciate your response and all the other responses. I have selected this answer as it is the closest to what I had already started. I was missing the 2 at the start. Thanks again for clearly showing the steps. – RexBanner Sep 13 '12 at 21:07
@RexBanner Anytime. – Pedro Tamaroff Sep 13 '12 at 22:05
@Peter Tamaroff: Does Cauchy-Schwarz state that $x_1y_1+x_2y_2+x_3y_3\leq \sqrt{x_1^2+x_2^2+x_3^3}\sqrt{y_1^2+y_2^2+y_3^3}$? And I don't think that your first example is a good one for what Cauchy-Schwarz inequality is. (Chris). – user 1618033 Sep 16 '12 at 11:54

For any $x_i, x_j, y_i, y_j$ we have $$(x_i y_j - x_j y_i)^2 = x_i^2 y_j^2 - 2 x_i x_j y_i y_j + x_j^2 y_i^2 \geq 0$$ which gives $$x_i^2 y_j^2 + x_j^2 y_i^2 \geq 2 x_i x_j y_i y_j.$$

Then for $x,y \in \mathbb{R}^n$ (ie, not just $\mathbb{R}^3$): $$2(\sum_{i=1}^n x_i y_i)^2 = 2\sum_{i=1}^n \sum_{j=1}^n x_i x_j y_i y_j \leq \sum_{i=1}^n \sum_{j=1}^n (x_i^2 y_j^2 + x_j^2 y_i^2) = 2(\sum_{i=1}^n x_i^2)(\sum_{i=1}^n y_i^2)$$

Dividing by $2$ and taking square roots gives the desired result.

share|cite|improve this answer
It would be good if you could explain the indices notation. – Pedro Tamaroff Sep 13 '12 at 1:45
@PeterTamaroff: Thanks for the edits. I hope the above clarifies... – copper.hat Sep 13 '12 at 1:50

Well...the cauchy-schwarz inequality states that $|\vec{a}\cdot \vec{b}|\leq ||\vec a|| ||\vec b||$.

Well, we know that $\vec{a}\cdot \vec{b} = ||\vec a||||\vec b||cos\theta$.
$cos\theta$ can be 1 at most and -1 at least, and so that means that $|\vec{a}\cdot \vec{b}|\leq ||\vec a|| ||\vec b||$.

As simple as that =)

My solution assumes that you know that $\vec{a}\cdot \vec{b} = ||\vec a||||\vec b||cos\theta$. If you need to prove that, that is a quick geometric proof where you graph any $\vec a$ and and any $\vec b$ and you make the vector $\vec a + \vec b$ and you use the law of cosines in order to get that expression.

share|cite|improve this answer

Let $f(t)$ be the square of the distance from $(x,y,z)$ to $(ta,tb,tc)$. Note that $f(t)\ge 0$ for all $t$. But by the standard distance formula, we have $$f(t)=(ta-x)^2+(tb-y)^2+(tc-z)^2.\tag{$1$}$$ Expand. We find that $$f(t)=t^2(a^2+b^2+c^2)-2t(ax+by+cz)+x^2+y^2+z^2.$$ The above quadratic is always $\ge 0$ precisely if the discriminant $$4(ax+by+cz)^2-4(a^2+b^2+c^2)(x^2+y^2+z^2)$$ is $\le 0$. That gives the desired inequality.

We also can get the condition for equality out of this. The discriminant is $0$ precisely if $f(t)=0$ has a double root $t_0$. that is the case iff $x=at_0$, $y=bt_0$, and $z=ct_0$, that is, precisely if the vector $(x,y,z)$ is a multiple of $(a,b,c)$.

Remark:: We cheated, basically the same proof works in $\mathbb{R}^n$ for any $n$. We do not even have to know the distance formula, since we can just define $f(t)$ as in Equation $(1)$.

share|cite|improve this answer
Condition on discriminant should be less than or equal to zero? – Robert Miller Sep 13 '12 at 0:59
@RobertMiller: Thanks for catching it! Fixed. – André Nicolas Sep 13 '12 at 1:09

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.